Anticholestatic mechanisms of ursodeoxycholic acid in lipopolysaccharide-induced cholestasis - Razori, María Valeria (2019)
Lipopolysaccharide (LPS) from Gram (-) bacteria induces inflammatory cholestasis by impairing the expression/localization of transporters involved in bile formation (e.g., Bsep, Mrp2). Therapeutic options for this disease are lacking. Ursodeoxycholic acid (UDCA) is the first choice therapy in cholestasis, but its anticholestatic efficacy in this hepatopathy remains to be evaluated. To asses it, male Wistar rats received UDCA for 5 days (25 mg/Kg/day, i.p.) with or without LPS, administered at 8 a.m. of the last 2 days (4 mg/Kg/day, i.p.), plus half of this dose at 8 p.m. of the last day. Then, plasma alkaline phosphatase (ALP), bile flow, basal and taurocholate-stimulated bile acid output, total glutathione output, and total/plasma membrane liver protein expression of Bsep and Mrp2 by confocal microscopy were assessed. mRNA levels of both transporters were assessed by Real-Time PCR. Plasma pro-inflammatory cytokines (IL-6 and TNF-α) were measured by ELISA. Our results showed that UDCA attenuated LPS-induced ALP plasma release and the impairment in the excretion of the Bsep substrate, taurocholate. This was associated with an improved Bsep expression at both mRNA and protein levels, and by an improved localization of Bsep in plasma membrane. UDCA failed to reduce the increase in plasma pro-inflammatory cytokines induced by LPS and Mrp2 expression/function. In conclusion, UDCA protects the hepatocyte against the damaging effect of bile acids accumulated by the LPS-induced secretory failure. This involved an enhanced synthesis of Bsep and an improved membrane stability of the newly synthesized transporters.